Interest-Bearing Currency and Legal Restrictions Theory: Lessons from the Southern Confederacy - Richard C.K. Burdekin; Marc D. Weidenmier (Claremont McKenna College, Department of Economics, 1999)
Instances of interest-bearing currency are relatively rare. The Southern Confederacy issued both interest and non-interest-bearing notes during the Civil War. The two types of notes apparently circulated alongside one another with the interest-bearing currency generally commanding the premium implied by legal restrictions theory. Government-imposed restrictions on banks prevented the non-interest-bearing notes from being driven out of circulation. The Southern experience appears to be consistent with the legal restrictions theory of money and suggests a potential role for interest-bearing currency as a circulating medium.
Keywords: 330